Consequences of New Approach to Chemical Stability Tests to Active Pharmaceutical Ingredients - Jamrógiewicz, Marzena (Frontiers in Pharmacology, 2016)
There is a great need of broaden look on stability tests of active pharmaceutical ingredients (APIs) in comparison with current requirements contained in pharmacopoeia. By usage of many modern analytical methods the conception of monitoring the changes of APIs during initial stage of their exposure to harmful factors has been developed. New knowledge must be acquired in terms of identification of each degradation products, especially volatile ones. Further research as toxicology prediction during in silico studies of determined and identified degradation products is necessary. In silico methods are known as computational toxicology or computer-assisted technologies which are used for predicting toxicology of pharmaceutical substances such as impurities or degradation products. This is a specialized software and databases intended to calculate probability of genotoxicity or mutagenicity of these substances through a chemical structure-based screening process and algorithm specific to a given software program. Applying of new analytical approach is proposed as the usage of PAT tools, XRD, HS-SPME GC-MS/MS, LC-MS/MS for stability testing. Described improvements should be taken into account in case of each drug existing already in the market as well as being implemented as new one.